Changes in metabolism but not myocellular signaling by training with CHO-restriction in endurance athletes - Gejl, K. D.; Vissing, K.; Hansen, M.; Thams, L.; Rokkedal-Lausch, T.; Plomgaard, P.; Meinild Lundby, A.-K.; Nybo, L.; Jensen, K.; Holmberg, H. C.; Ørtenblad, N. (Physiological Reports, 2018)
Carbohydrate (CHO) restricted training has been shown to increase the acute training response, whereas less is known about the acute effects after repeated CHO restricted training. On two occasions, the acute responses to CHO restriction were examined in endurance athletes. Study 1 examined cellular signaling and metabolic responses after seven training-days including CHO manipulation (n = 16). The protocol consisted of 1 h high-intensity cycling, followed by 7 h recovery, and 2 h of moderate-intensity exercise (120SS). Athletes were randomly assigned to low (LCHO: 80 g) or high (HCHO: 415 g) CHO during recovery and the 120SS. Study 2 examined unaccustomed exposure to the same training protocol (n = 12). In Study 1, muscle biopsies were obtained at rest and 1 h after 120SS, and blood samples drawn during the 120SS. In Study 2, substrate oxidation and plasma glucagon were determined. In Study 1, plasma insulin and proinsulin C-peptide were higher during the 120SS in HCHO compared to LCHO (insulin: 0 min: +37%; 60 min: +135%; 120 min: +357%, P = 0.05; proinsulin C-peptide: 0 min: +32%; 60 min: +52%; 120 min: +79%, P = 0.02), whereas plasma cholesterol was higher in LCHO (+15-17%, P = 0.03). Myocellular signaling did not differ between groups. p-AMPK and p-ACC were increased after 120SS (+35%, P = 0.03; +59%, P = 0.0004, respectively), with no alterations in p-p38, p-53, or p-CREB. In Study 2, glucagon and fat oxidation were higher in LCHO compared to HCHO during the 120SS (+26-40%, P = 0.03; +44-76%, P = 0.01 respectively). In conclusion, the clear respiratory and hematological effects of CHO restricted training were not translated into superior myocellular signaling after accustomization to CHO restriction.